Zusanli(ST 36) Acupoint Injection with Neostigmine for Sepsis Acute Gastrointestinal Injury - Xiong, Fu; Zhang, Jingyi; Gao, Peiyang (Journal of Contemporary Medical Practice, 2024)
Sepsis is life-threatening organ dysfunction caused by a dysregulated host response to infection. Acute gastrointestinal injury is a common complication of sepsis and one of the major causes of high mortality in sepsis. However, the treatment of acute gastrointestinal injury is limited and the effect is not ideal. Acupoint injection is a traditional Chinese medicine characteristic therapy that injects liquid or drug into acupoints, which can treat multiple system diseases. Compared with traditional acupuncture or intramuscular injection, Acupoint injection effect is more lasting. We provide a method for the treatment of acute gastrointestinal injury other than intravenous and gastrointestinal routes, which is simple and easy to operate. It may have a positive effect on the treatment of acute gastrointestinal injury in sepsis by injecting neostigmine into the acupoint within Zusanli (ST 36), and provide support for the treatment activities of traditional ethnic medicine entering the intensive care unit (ICU).